Bezpieczeństwo społeczne jako element warunkujący bezpieczeństwo państwa .......... 133 - Miernik, Rafał (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
Social security is a category that relatively recently appeared in the area of sciences dealing with national security and is a permanent element conditioning the security of a democratic country. It has found itself in the field of interest among others, economists, political scientists, sociologists, resulting in a variety of its perceptions, but also seeking answers to the question: what the importance of social security for the security of the state is.